PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMP TENTANG HUKUM ARCHIMEDES - Sinta Sutiyani; Edy Tandililing; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research was conducted to improve the learning outcomes of eighth grade students of SMP Negeri 2 Putussibau on Archimedes law through the application of a pictorial riddle-assisted inquiry model. The form of this research was quasy experimental design with pretest-posttest control group design, which involved 24 students of class VIII C (control class) and 24 students of class VIII D (experimental class) of SMP Negeri 2 Putussibau. Learning outcome data obtained through 10 essay test questions and analyzed using independent samples test with a significance level of 5% preceded by analysis prerequisite tests, obtained sig values. (0.012 <0.05) these results indicated that there were differences in student learning outcomes between the experimental class and the control class. Improved learning outcomes in the experimental class were analyzed using the N-Gain score and an increase of 0.47 (moderate category) was obtained. This research is expected to be an alternative for teachers to improve learning outcomes in science-physics learning, especially in conceptual material. Keywords: Archimedes Law, Learning Outcomes, Pictorial Riddle-Assisted   Inquiry Model